Gender, Parenthood, and Perceived Chances of Promotion. (August 2017) - Wynn, Alison T.
In this article, I examine the gender gap in perceived promotion chances. Using General Social Survey data, I find that men are more likely than women to expect a promotion, and work-family conflict partially explains this gap. Because men work longer hours and have fewer family responsibilities, they anticipate higher promotion chances. I then explore the interaction of gender and parental status. I find that men and childless women expect higher promotion chances when they work longer hours, but the same is not true for mothers. Working long hours may violate stereotypes dictating that mothers should devote themselves primarily to caregiving, thereby decreasing mothers' promotion expectations relative to other groups.